2015
DOI: 10.1016/j.bmhimx.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

ADIPOQ and ADIPOR2 gene polymorphisms: association with overweight/obesity in Mexican children

Abstract: The presence of rs11061971 of ADIPOR2 variant confers protection against obesity and could be used as a marker in Mexican children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
2
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
2
3
2
4
Order By: Relevance
“…The authors found that the ADIPOQ-rs2241766 genetic variant was associated with obesity in the overall populations (GG v. TT, OR = 1•39, 95 % CI 1•11, 1•73) (46) . On the other hand, some cross-sectional studies reported results different from those found in our longitudinal analysis (20,47) . In a cross-sectional study on 1469 Mexican children aged 6-12 years, the authors observed no association between the ADIPOQ-rs2241766 gene variant and overweight/ obesity (20) .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The authors found that the ADIPOQ-rs2241766 genetic variant was associated with obesity in the overall populations (GG v. TT, OR = 1•39, 95 % CI 1•11, 1•73) (46) . On the other hand, some cross-sectional studies reported results different from those found in our longitudinal analysis (20,47) . In a cross-sectional study on 1469 Mexican children aged 6-12 years, the authors observed no association between the ADIPOQ-rs2241766 gene variant and overweight/ obesity (20) .…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, some cross-sectional studies reported results different from those found in our longitudinal analysis (20,47) . In a cross-sectional study on 1469 Mexican children aged 6-12 years, the authors observed no association between the ADIPOQ-rs2241766 gene variant and overweight/ obesity (20) . Another cross-sectional study including 453 Turkish children and adolescents aged 6-17 years also found no difference in the TT (wild type) or non-TT (TG þ GG) genotype between the obese and non-obese groups (47) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the results of this meta-analysis suggested that polymorphisms in the adipokine genes, ADIPOQ, IL-1β, IL-6, and TNF-α , increase the risk of obesity [19]. Our results are consistent with three studies in Mexican children that showed no contribution of several polymorphisms in ADIPOQ gene (rs2241766, rs182052, rs266729, and rs822393) in children obesity [9, 20, 21]. A similar effect was observed in TNF-α and interleukin-10 [22], suggesting that genetic variants in adipokines do not have a significant effect in Mexican-Mestizo children obesity.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning biochemical parameters, we found an altered lipid profile when either BMI or BFP was used to classify obesity, while higher HbA1c levels were found in the obesity group only when BFP was the classification criterion. These results are in agreement with the previous studies in Mexican children reported by Aradillas-García et al [ 29 ] and Peralta-Romero et al [ 30 ], where BMI was also the obesity diagnosis criterion; they found that glucose, total cholesterol, LDL cholesterol, and triglycerides were significantly higher and that HDL was lower in the obesity group compared with the normal-weight group.…”
Section: Discussionsupporting
confidence: 93%